THE TABERNACLE AS THE PLACE OF GOD'S PRESENCE AMONG HIS PEOPLE: Introduction to the Biblical History of the Tabernacle - Wonoadi, Jusak Pundiono; Tandana, Ester Agustina (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2021)
The tabernacle is a Biblical institution as a place of God's presence among His people that was not suddenly created, just as the existence of God's people itself has historical traces and did not suddenly form. This paper provides a chronological view of God's presence until His presence is accommodated by an institution as the place where God dwells called the Tabernacle. The chronology will be discussed from the point of view of Biblical history by presenting facts that state explicitly or implicitly regarding the presence of God, and which are also related to the promise in the